Bidang Garapan Sarana dan Prasarana Dalam Administrasi Pendidikan - Purba, Atikah Zahrani; Nasution, Fadhilah Hilmy; N, Nurhafizah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The area of developing facilities and infrastructure in educational administration is very important to support the achievement of learning objectives. Learning activities will run smoothly if educational facilities and infrastructure are adequate. The research method used is a qualitative method with literature study. The results of the research show that the field of facilities and infrastructure in educational administration aims to strive for the procurement of educational facilities and infrastructure through comprehensive planning and procurement systems, seeking appropriate and efficient use of school facilities and infrastructure. The principles in the field of facilities and infrastructure in educational administration include the principle of achieving goals, the principle of efficiency, the principle of administration, the principle of clarity of responsibility and the principle of cohesiveness. The scope of the field of facilities and infrastructure in educational administration is planning, procurement, inventory, maintenance and disposal.